1987
DOI: 10.1111/j.1600-0447.1987.tb02794.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet serotonin levels in panic disorder

Abstract: Platelet serotonin levels were examined in 18 patients with panic disorder and compared to platelet serotonin levels of eight healthy controls. There was no statistically significant difference in the platelet serotonin levels between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Elevations (Giannini et al, 1983;Davis et al, 1985) as well as decreases (Evans et al, 1985) of plasma serotonin, and decreased urinary 5-HIAA (Giannini et al, 1983), have been reported in small groups of anxious individuals. Platelet serotonin uptake has been reported to be abnormal in panic patients (Norman et al, 1986), but platelet serotonin levels were normal (Balon et al, 1987). Finally, plasma HVA, a metabolite of dopamine, was not significantly elevated in panic patients (Roy-Byrne et al, 1986a); however, a bimodal distribution was observed, with the most anxious patients tending to have higher concentrations.…”
Section: Psychoendocrine Findingsmentioning
confidence: 93%
“…Elevations (Giannini et al, 1983;Davis et al, 1985) as well as decreases (Evans et al, 1985) of plasma serotonin, and decreased urinary 5-HIAA (Giannini et al, 1983), have been reported in small groups of anxious individuals. Platelet serotonin uptake has been reported to be abnormal in panic patients (Norman et al, 1986), but platelet serotonin levels were normal (Balon et al, 1987). Finally, plasma HVA, a metabolite of dopamine, was not significantly elevated in panic patients (Roy-Byrne et al, 1986a); however, a bimodal distribution was observed, with the most anxious patients tending to have higher concentrations.…”
Section: Psychoendocrine Findingsmentioning
confidence: 93%
“…The literature regarding serotonergic function in anxiety disorders is in disagreement. In PD, platelet 5‐HT uptake has been reported to be abnormally elevated (146), normal (147) or abnormally reduced (148). Platelet imipramine binding (to a site related to the 5‐HT transporter site) did not differ in the PD group relative to those in the control group (149, 150).…”
Section: Serotonergic Function In Anxiety Disordersmentioning
confidence: 99%
“…Evans and coworkers [26] reported lowered plasma serotonin concentrations while Balon et a1 [27] found no difference in platelet serotonin concentrations between panic patients and controls. The present study has shown an abnormality of serotonin function in panic disorder.…”
Section: Discussionmentioning
confidence: 99%